INCREASE STUDENT ACTIVENESS AND LEARNING OUTCOMES USING PROBLEM BASED LEARNING ASSISTED BY IMAGE MEDIA - Oktafiani, Inke; Gunawan, Gunawan; Akhsani, Lukmanul; Kusuma, Jaka Wijaya; Sugihandardji, Chumaedi; Widiyastuti, Erni (International Journal of Economy, Education and Entrepreneurship (IJE3), 2024)
The study aims to improve student activeness and learning outcomes using problem-based learning (PBL) assisted by image media in science subjects. The research subjects used were grade IV students of SD Negeri 1 Kedungbanteng. The research method used is classroom action research which consists of planning, action, observation, and reflection stages. The steps of implementing the PBL model with image media are carried out in five steps. The data collection techniques used are non-test techniques in the form of observation and interviews, and test techniques in the form of written tests. Observation sheets and interview guidelines were used to collect data on the application of PBL models with image media and learning activity. There was an increase in the application of PBL with image media to teachers in the first cycle by 84.37%, the second cycle by 90.62%. In the observation of the activities of students in cycle I as much as 82.5%, cycle II as much as 87.5%. The activeness of students in meeting 1 increased from the very high category of 27%, high 43%, increased to the very high category of 43%, high 57% in meeting 2 cycle II. The results of learning science cycle I meeting 1 the percentage of completion on the pretest is 20%, the increase in the posttest is 80% In meeting 2, the percentage of completion of the pretest by 23% increases on the posttest by 87%. In cycle II meeting 1, the percentage of completion in the pretest was 33.33%, an increase in the posttest was 86.67% In meeting 2, the percentage of complete pretest was 40%, increased in the posttest by 90%